Pokemon : the winner's cup - West, Tracey (London : Orchard Books, 2021)
It's time! With all four star gems under his belt, Pokemon master-in-training Ash Ketchumis now ready for the biggest battle of his life-the Winner's Cup. Can Ash and Pikachu overcome the mighty Dragonite to win the ultimate Pokemon challenge?
Keywords: Pokemon. -- Juvenile Literature